Effectiveness of ALK inhibitors in treatment of CNS metastases in NSCLC patients. (31st December 2023) - Gil, Michał; Knetki-Wróblewska, Magdalena; Niziński, Przemysław; Strzemski, Maciej; Krawczyk, Paweł
Abstract: Metastases to the central nervous system (CNS) in patients with non-small cell lung cancer constitute an extremely difficult clinical problem, and their occurrence is associated with a poor prognosis. Due to the existence of the blood-brain barrier (BBB) and the action of proteins responsible for the transport of drugs, e.g. P-glycoprotein (P-gp), the penetration of drugs into the CNS is insufficient. Until recently, the only method of CNS metastases treatment was radiotherapy and neurosurgery. The advancement of molecular biology allowed discover targets for molecularly targeted therapies. One of targets is abnormal anaplastic lymphoma kinase, which results from the rearrangement of the ALK gene in patients with non-small cell lung cancer (NSCLC). ALK rearrangement occurs in only about 4.5% of NSCLC patients, but its presence favors brain metastases. The ALK inhibitors (ALKi) were modified to obtain molecules with high ability to penetrate into the CNS. This was achieved by modifying the structure of individual molecules, which became, inter alia, less substrates for P-gp. These modifications caused that less than 10% of patients experience progression in CNS during new ALK inhibitors treatment. This review summarizes the knowledge about the action of BBB, the pharmacodynamics and pharmacokinetics of ALKi, with particular emphasis on their ability to penetrate the CNS and the intracranial activity of individual drugs from different generations of ALK inhibitors. KEY MESSAGES: ALK gene rearrangement favors the development of central nervous system (CNS) metastases in patients with NSCLC. New generations of ALK inhibitors penetrate the CNS and induce an intracranial response and protect against new brain lesions.